Hubungan Antara Peran Pengawas Minum Obat (Pmo) Dengan Kepatuhan Kunjungan Berobat Pada Pasien Tuberculosis Paru (Bb Paru) Di Puskesmas Nogosari Boyolali - Prabowo, Rivangga Dwi Ratna, Irdawati, S.kep., Ns., Msi, Med, Wachidah Yuniartika, S.kep Ns (2014)
Support families and communities have a major role in improving treatment adherence is to oversee and supported in patients. Advantages family as Supervisory Drink Drugs (SDD) is a stay at home with the patient so that a more optimal monitoring and direct, requiring no transportation costs. This study aimed to determine the relationship between the role of the Supervisory Drink Drugs (SDD) to the patient treatment compliance visit Pulmonary Tuberculosis (TB Lung) in PHC Nogosari Boyolali. This study design with cross cross-sectional approach. The population in this study were all patients with TB were recorded in health centers that have Nogosari Boyolali SDD, sampling technique used is total sampling, so that the whole population is used as a sample. The analytical tool used by the Chi-square test (2). The results reveal that: 1) The role of the Supervisory Drink Drugs (SDD) in patients with pulmonary tuberculosis (pulmonary TB) in PHC Nogosari Boyolali included in both categories; 2) Visit Pulmonary Tuberculosis patients (pulmonary TB) in health centers included in the category Nogosari Boyolali obedient; and 3) There is a relationship between the role of the Supervisory Drink Drugs ((SDD) to the patient's compliance with treatment visit Pulmonary Tuberculosis (pulmonary TB) in PHC Nogosari Boyolali (p = 0.033).